2009
DOI: 10.1186/bf03353171
|View full text |Cite
|
Sign up to set email alerts
|

Validity on radar observation of middle- and upper-atmosphere dynamics

Abstract: Doppler radar observations have made a large contribution towards improving our understanding of middleand upper-atmosphere dynamics. This radar echo is mainly due to radiowave scattering by atmospheric turbulence, which occurs almost universally throughout the atmosphere as a result of gravity wave (GW) breaking. In the strictness sense, the radar pulse is back-scattered by radio refractive index (RRI) perturbations caused by turbulence whose size along the radar beam is half of the radar wavelength. Understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…The advent of Mesosphere‐Stratosphere‐Troposphere (MST) radar makes it possible to observe the mesosphere by radio waves (Hocking, 1997). Due to photo‐ionized electrons in the upper mesosphere, the MST radar can receive the echoes in Very‐High‐Frequency (VHF) band through the turbulent scattering (Kato, 2009). In the daytime, the MST radar can receive much more scattered echoes from the mesospheric turbulent irregularities as the solar radiation has ionized neutral atmospheric components in the D‐layer.…”
Section: Introductionmentioning
confidence: 99%
“…The advent of Mesosphere‐Stratosphere‐Troposphere (MST) radar makes it possible to observe the mesosphere by radio waves (Hocking, 1997). Due to photo‐ionized electrons in the upper mesosphere, the MST radar can receive the echoes in Very‐High‐Frequency (VHF) band through the turbulent scattering (Kato, 2009). In the daytime, the MST radar can receive much more scattered echoes from the mesospheric turbulent irregularities as the solar radiation has ionized neutral atmospheric components in the D‐layer.…”
Section: Introductionmentioning
confidence: 99%
“…Atmospheric radars which receive echoes from fluctuations of refractive index are useful for directly observing height profiles of vertical and horizontal winds both in clear and cloud regions (Fukao, 2007). Mesosphere-Stratosphere-Troposphere (MST) atmospheric radars (hereafter MST radars) to observe winds and turbulence up to the mesosphere are useful for observing uppertropospheric winds with high time and vertical resolutions (Kato, 2009). It has been shown that a combination of atmospheric radar and cloud profiling radar is useful for knowing dynamical processes in and around cirriform clouds (Yamamoto et al, 2008).…”
Section: Introductionmentioning
confidence: 99%